Kontribusi Guru Dalam Memberikan Motivasi Belajar Pendidikan Karakter Peserta didik - Rahma, Siti; Leksono, Aris Adi; Zamroni, M Afif (Journal of Education and Learning Innovation, 2024)
This study aims to explore the religious character values instilled in students at MI Al Hidayah Bangli and the strategies applied in shaping these characters through religious activities. This research uses qualitative methods with data collection techniques through interviews, observation, and documentation. The results revealed nine religious character values developed, namely righteousness, courtesy, honesty, responsibility, gratitude, sincerity, humility, discipline, respect for time, care and respect, as well as respect for other people's opinions and being able to work together. The strategies implemented include exemplifying discipline habituation, creating a conducive environment, and integrating and internalizing character values in various religious activities. These strategies positively impact students by increasing good character, social spirit, honesty, justice, consistency, and loyalty. This study concludes that MI Al Hidayah Bangli seeks to instill and develop religious character in students through various strategies in religious activities that are carried out consistently and continuously and have a positive impact on the development of student character, which is expected to be implemented in everyday life.